But it's against the rules!! Structured competitive games as a neglected resource in child psychodynamic psychotherapy. - Maroudas, Celine (International Journal of Psychoanalysis, 2025)
In the field of child psychoanalytic psychotherapy, structured competitive games such as Monopoly, UNO or football have traditionally been regarded as less conducive to deep psychodynamically oriented work. By contrast, some contemporary authors have pointed out that in middle childhood it is often precisely in play with structured games – game-play – that spontaneity and strong emotions come to the fore. These authors suggest that game-play constitutes a potentially powerful therapeutic tool for access to, and communication with, the older child's inner world. In this paper, clinical theoretical arguments are presented alongside clinical examples in support of this view and a variety of forms of game-play encountered in the analytic playroom are discussed and analysed. The paper examines how the rules and partially predetermined content of these games act as a framing structure in which the analytic work can take place safely and spontaneously, and how the model of the container ↔ contained can be usefully applied to game-play in the child therapy room. Emphasis is placed throughout on the therapeutic role of a flexible and carefully calibrated approach to the game's rules and structure and the child's cheating.